The Impact of Foreign Direct Investment on Economic Growth - An Empirical Analysis of Different Effects in Less and More Developed Countries - Thomas Brenner (Philipps-University Marburg, Department of Geography, 2014)
This paper studies the effects of foreign direct investment (FDI) on national economic growth with the help of GMM panel regressions. Effects on productivity growth, capital and labor inputs as well as innovation activities are distinguished. Furthermore, less and more developed countries as well as the time periods 1974-1991 and 1992-2009 are studied separately. Effects of FDI on production capacities are found for more developed countries in the first time period, while effects on innovation activities are found for the medium developed countries in the latter time period. Effects in less developed countries are rather negative.
Keywords: O11; O40; E10; C23; F23; 330; growth; foreign direct investment; FDI; growth effects; panel GMM